Reversible DNA Compaction - González-Pérez, Alfredo (Current Topics in Medicinal Chemistry, 2014)
In this review we summarize and discuss the different methods we can use to achieve reversible DNA compaction in vitro. Reversible DNA compaction is a natural process that occurs in living cells and viruses. As a result these process long sequences of DNA can be concentrated in a small volume (compacted) to be decompacted only when the information carried by the DNA is needed. In the current work we review the main artificial compacting agents looking at their suitability for decompaction. The different approaches used for decompaction are strongly influenced by the nature of the compacting agent that determines the mechanism of compaction. We focus our discussion on two main artificial compacting agents: multivalent cations and cationic surfactants that are the best known compacting agents. The reversibility of the process can be achieved by adding chemicals like divalent cations, alcohols, anionic surfactants, cyclodextrins or by changing the chemical nature of the compacting agents via pH modifications, light induced conformation changes or by redox-reactions. We stress the relevance of electrostatic interactions and self-assembly as a main approach in order to tune up the DNA conformation in order to create an on-off switch allowing a transition between coil and compact states. The recent advances to control DNA conformation in vitro, by means of molecular self-assembly, result in a better understanding of the fundamental aspects involved in the DNA behavior in vivo and serve of invaluable inspiration for the development of potential biomedical applications.
Keywords: compaction